2016
DOI: 10.1177/0885328216654425
|View full text |Cite
|
Sign up to set email alerts
|

Daunomycin-loaded superparamagnetic iron oxide nanoparticles: Preparation, magnetic targeting, cell cytotoxicity, and protein delivery research

Abstract: The clinical use of daunomycin is restricted by dose-dependent toxicity and low specificity against cancer cells. In the present study, modified superparamagnetic iron oxide nanoparticles were employed to load daunomycin and the drug-loaded nanospheres exhibited satisfactory size and smart pH-responsive release. The cellular uptake efficiency, targeted cell accumulation, and cell cytotoxicity experimental results proved that the superparamagnetic iron oxide nanoparticle-loading process brings high drug targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Current investigations have also synthesized IONPs employing different shells with anticancer agents conventionally administered, such as β-cyclodextrin [ 135 ], carmustine [ 136 ], cetuximab [ 137 , 138 , 139 ], cytarabine [ 140 ], daunomycin [ 141 ], docetaxel [ 142 , 143 ], epirubicin [ 144 ], 5-fluorouracil [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ], gemcitabine [ 22 , 154 , 155 , 156 , 157 , 158 ], methotrexate [ 159 , 160 , 161 ], mitoxantrone [ 162 , 163 , 164 , 165 ] and paclitaxel [ 27 , 104 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. It is noteworthy, however, that these nanosystems demonstrate magnetic properties only in the presence of external magnetic fields to prevent agglomerations of nanoparticles [ 111 ] and to allow a satisfactory performance in the target sites.…”
Section: Drugs Bound To Ionpsmentioning
confidence: 99%
“…Current investigations have also synthesized IONPs employing different shells with anticancer agents conventionally administered, such as β-cyclodextrin [ 135 ], carmustine [ 136 ], cetuximab [ 137 , 138 , 139 ], cytarabine [ 140 ], daunomycin [ 141 ], docetaxel [ 142 , 143 ], epirubicin [ 144 ], 5-fluorouracil [ 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ], gemcitabine [ 22 , 154 , 155 , 156 , 157 , 158 ], methotrexate [ 159 , 160 , 161 ], mitoxantrone [ 162 , 163 , 164 , 165 ] and paclitaxel [ 27 , 104 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ]. It is noteworthy, however, that these nanosystems demonstrate magnetic properties only in the presence of external magnetic fields to prevent agglomerations of nanoparticles [ 111 ] and to allow a satisfactory performance in the target sites.…”
Section: Drugs Bound To Ionpsmentioning
confidence: 99%
“…11 Considering MNP modeling relevant to cancer, studies have shown that a variety of chemotherapeutic drugs can be bound to, and transported by MNPs. [60][61][62][63] MNP-chemotherapy constructs have demonstrated growth-inhibitory effects in vitro and in animal studies for many types of cancer cells, including glioblastoma. 2,[64][65][66] Ingenious larger nanostructures ("micro-robots") which can be actuated by external magnetic fields have also been described, with the goal of targeting drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Fe 3 O 4 Nps were synthesized by a coprecipitation of ferric and ferrous chlorides in alkaline medium following the method we have previously reported. 22 Fe 3 O 4 @SiO 2 core-shell nanocomposites were fabricated via sol-gel process of hydrolysis and condensation of TEOS. Briefly, 50 mg Fe 3 O 4 compound was transferred to a beaker, dispersed in 30 ml water, assisted with ultrasounds.…”
Section: Experimental Methodsmentioning
confidence: 99%